PlomBOX: a low cost bioassay for the sensitive detection of lead in drinking water - A. Dias; M. Alvarez; Y. Gándola; A. Deisting; E. Alba Posse; H. Arnaldi; H. Asorey; X. Bertou; A. Colque; F. Favela-Pérez; J. Gasulla; M. Gómez Berisso; et al. (Communications Engineering)
Abstract This paper reports the design of a biosensor for sensitive, low-cost measurement of lead in drinking water. The biosensor uses a genetically-modified strain of Escherichia coli, which serves as both signal amplifier and reporter of lead in water, measured via colour change. We developed the PlomBOX measurement platform to image this colour change and we demonstrate its capability to detect concentrations as low as the World Health Organisation upper limit for drinking water of 10 ppb. Our approach does not require expensive infrastructure or expert operators, and its automated sensing, detection and result visualisation platform is user-friendly and robust compared to existing lead biosensors—critical features to enable measurement by non-experts at the point of use.